Analysis of Technology-Based Human Capital towards Increasing Innovation at PT PLN (Persero) UP3 Palopo - Ainul Rahma; Saharuddin Saharuddin; Dirham Dirham (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the effect of technology-based human capital management on increasing innovation at PT PLN (Persero) UP3 Palopo. Methodology: Using a quantitative approach with a causal design, this study examines the relationship between technology in human capital management and the resulting innovation. Data were obtained through questionnaires and analyzed by simple linear regression method using statistical software. Results: The results showed that technology-based human capital management has a positive and significant impact on innovation in the company. Findings: This finding confirms that the application of technology in the human resource management system can improve work effectiveness and encourage a more innovative environment. Novelty & Originality: The novelty of this study lies in its focus on technology-based human capital management within a regional service unit of a state-owned electricity company in Palopo, a context that has received limited empirical attention in prior research. Its originality emerges from the examination of how digital human resource systems directly influence innovation outcomes in the energy sector, specifically within the Indonesian state-owned enterprise environment. Conclusions: The practical implications of this study include the need for greater investment in human capital management technology as well as improved training programs to create a more adaptive and collaborative work culture in the energy sector. The study concludes that integrating technology into human capital management is a strategic imperative for fostering innovation and organizational competitiveness. Type of Paper: This paper is an empirical research paper.